An epidemiologic surveillance study based on wastewater and respiratory specimens reveals influenza a virus prevalence and mutations in Taiyuan, China during 2023–2024 - Lifeng Zhao; Jihong Xu; Jiane Guo; Ping Zhang; Xiaofang Guo; Zhihong Zuo; Li Gao; Zhao Jia; Puna Xue; Jitao Wang (BMC Infectious Diseases)
Abstract Background Influenza is a major cause of morbidity and mortality. Influenza A virus (IAV) is one of the most important pathogens causing influenza and often causes global pandemics due to its tendency to mutate. We aim to use epidemiology based on wastewater and respiratory specimens to understand the occurrence of influenza A virus infections in Taiyuan City. Methods A retrospective epidemiology surveillance was carried out at the First Hospital of Shanxi Medical University (FHSMU) and five wastewater treatment plants (WTPs) in Taiyuan city from 2023 to 2024. Reverse transcription real-time fluorescence quantitative polymerase chain reaction (RT-qPCR) was used to detect influenza A viruses in wastewater and respiratory specimens. High-throughput whole genome sequencing was performed on 17 strains obtained in this study, and subsequent analyses included characterization, phylogenetic construction, amino acid mutation analysis, and antigenic structural variability assessment. Results 520 wastewater samples and 1,203 throat swab samples were collected. We detected RNA concentration from pH1N1 and H3N2 viruses in wastewater and got 17 genome sequences (5 of pH1N1 and 12 of H3N2) in respiratory specimens. Whole-genome sequencing showed co-prevalence of pH1N1 viruses in the branches of 6B.1 A.5a.2a.1 and H3N2 viruses in the branches of 3 C.2a1b.2a.2a.3a.a in Taiyuan from 2023 to 2024. Moreover, a HA mutation (N138D), predicted to be of high phenotypic consequence, was found in 8 Taiyuan H3N2 sequences. Conclusion This study highlights the predominant presence of pH1N1 and H3N2 strains in Taiyuan. The analysis also identified amino acid site variations in the HA antigenic epitopes in H3N2 strains, which may contribute to immune escape.